HUBUNGAN MOTIVASI DALAM MEMBACA TERHADAP PEMAHAMAN TEKS MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR ANGKATAN 2013 - Maulia Septari; Otang Kurniaman; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstrack: This study was motivated by the motivation of students in reading contained in the education system that will foster student understanding of the text in the course PGSD University of Riau. Motivation to read is driving students to be enterprising activities in reading, while a text comprehension language skills are mastered to obtain readings meaning is understood primarily in a reading. The purpose of this study was to examine the relationship of motivation in reading the text comprehension of students of primary school teacher education class of 2013. Methods used in this study is quantitative. The study population was all students of the University of Riau PGSD force in 2013, amounting to 135 people. The samples were all students PGSD force in 2013 so this research is called the study population. The data collected in this study is the motivation for reading data from a questionnaire and a text understanding about the text. Based on the analysis of data, it can be concluded that There is a significant relationship between motivation in reading comprehension texts with students of the Faculty of Teacher Training and Education sub-program of study primary school teaching force in 2013, with the value of the correlation (rxy) of 0,277 are in the positive direction which lies in Low-level relationships and the acquisition value of tindicates that t count greater than 3,319 ttable 1,645 at 5% significance level. Thus the higher the motivation in the reading, the higher the level of understanding of the text and vice versa, the lower the motivation to read it will get worse also the understanding of the text.Keywords: Motivation In Reading, Comprehension TextWisuda Oktober